2011
DOI: 10.1210/jc.2010-0989
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Temperature, Age, Sex, Body Mass Index, and Diabetic Status Determine the Prevalence, Mass, and Glucose-Uptake Activity of 18F-FDG-Detected BAT in Humans

Abstract: The present study identifies outdoor temperature, age, sex, BMI, and diabetes status as determinants of the prevalence, mass, and glucose-uptake activity of (18)F-FDG-detected BAT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
437
5
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 496 publications
(476 citation statements)
references
References 26 publications
28
437
5
6
Order By: Relevance
“…In humans, several studies have recently shown negative correlations between BAT activity and adiposity [3,12,13] and age [14]. A negative association between BAT activity and diabetic status, independent of BMI and age, has also been reported in a retrospective study [15]. In addition, an impaired thermogenic response to mild cold has been found in diabetic women compared with obese women [16], suggesting a role for insulin resistance in mediating these impairments.…”
Section: Introductionmentioning
confidence: 79%
“…In humans, several studies have recently shown negative correlations between BAT activity and adiposity [3,12,13] and age [14]. A negative association between BAT activity and diabetic status, independent of BMI and age, has also been reported in a retrospective study [15]. In addition, an impaired thermogenic response to mild cold has been found in diabetic women compared with obese women [16], suggesting a role for insulin resistance in mediating these impairments.…”
Section: Introductionmentioning
confidence: 79%
“…Cypess et al used the same threshold [16]. However, Vosselman et al used a threshold of 1.5 g/ml [17] and van Marken Lichtenbelt et al reported that they used a 'set threshold' [8], whereas Carey et al and Ouellet et al considered an SUV >1.0 g/ml as BAT [18,19]. The lower the chosen threshold, the higher the observed volume of BAT will be.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies have indicated that BAT activity varies seasonally [4,25], we conducted trials for each individual within a 14 day period to avoid confounding effects of intra-individual seasonal variation. The mean daily maximum temperature for the month prior to trials did not differ between groups (lean 20.5±1.6°C; obese 20.6±1.6°C [mean ± SEM]) and there were no differences between the maximum temperature on the day before (lean group: placebo 23.1±2.1°C, ephedrine 19.4±1.3°C; obese group: placebo 21.4±2.1°C, ephedrine 20.2±2.4°C) or the minimum temperature on the night before (lean group: placebo 13.0±1.7°C, ephedrine 9.5±1.5°C; obese group: placebo 11.2±1.3°C, ephedrine 10.4±1.8°C) trials within or between groups.…”
Section: Methodsmentioning
confidence: 99%